Fostering emotional intelligence and self-regulation in gifted high school students: experimental evidence from a soft skills development program - Mukhametkairov, Arslanbek; Matayev, Berik; Kalimova, Assemgul; Utegenova, Meruyert; Ibraimova, Lira (Frontiers in Education, 2026)
IntroductionGifted adolescents often receive extensive cognitive enrichment, while their emotional and self-regulatory development remains underrepresented in school programs. This study examined whether socio-emotional and self-regulatory skills can be effectively developed through a structured soft skills intervention for gifted high school students.MethodsA seven-week soft skills program was implemented with 96 gifted students aged 15–16 in Kazakhstan. Participants were randomly assigned to an experimental group (n = 48), which engaged in reflection, empathy, and time-management activities, and a control group (n = 48), which continued regular instruction. Emotional intelligence, self-regulation, motivation, and communication skills were assessed using validated psychometric scales and expert observations (Cronbach’s α = 0.80–0.91). Data were analyzed using t-tests and ANCOVA.ResultsThe experimental group demonstrated statistically significant improvements compared to the control group (p < 0.001), particularly in emotional intelligence and self-regulation, with large effect sizes (η2 = 0.59–0.68). Expert evaluations also indicated increased emotional awareness, communication competence, and leadership behaviors among participants of the intervention.Discussion/conclusionThe findings indicate that socio-emotional and self-regulatory competencies in gifted adolescents can be effectively enhanced through structured experiential learning. The proposed program offers a practical and scalable framework for integrating soft skills training into secondary education curricula for gifted learners.